Buyer-seller relationship as a source of interactive learning and innovation: The Malaysian automotive industry perspective - Zainal Abidin, Che Rozenan; Ab. Rahman, Azmi (2006)
The paper looks at the buyer-seller relationship between Malaysian national car companies and their local automotive parts vendors as a source of interactive learning and innovation.Innovative activities are used as the measurement for interactive learning and innovation and the IMP interaction approach is used to analyze the interaction between the buyer and seller.Trust and commitment are the classic buyer-seller relationship variables that can lead to interactive learning and innovation.The research proposes a triangulation approach combining semi-structured interviews of focal relationships followed by a quantitative survey of the automotive parts vendors.